Effects of mindfulness training on university basketball players’ technical, tactical performance and mental fatigue - Cao, Shudian (2023)
Mental fatigue (MF) is a psycho-biological state caused by a prolonged period of demanding cognitive activity. The effects of MF on basketball performance were comprehensively investigated in the literature. However, the effects of MF on basketball technical and tactical performance and the recovery strategy to counteract MF and basketball performance remain unclear. The objective of this study is to investigate the effects of MF on basketball technical and tactical performance and mindfulness training on the recovery of MF, technical and tactical performance among university students. A pre- and post-test approach with cluster Randomized Controlled Trial (cRCT) was applied in this study. The sample size was calculated by the Software package G*Power3.1. Considering the design effect, 54 male basketball players (n=18 each group) were finally recruited from three universities and aged at 18-24 years were randomly assigned into control group (CG), mental fatigue group (MFG) and mental fatiguemindfulness group (MF-MG). A 30-min Stroop task was first used to induce MF in MFG and MF-MG. Then, the 30-min brief audio mindfulness training was applied in MF-MG. MF and mindfulness state were measured by visual analog scale (VAS) and five facet mindfulness questionnaire (FFMQ) respectively. The basketball performance was recorded in the small side game (SSG). The results from Generalized Estimating Equations (GEE) indicated that MF significantly influenced the attention level with the significant decrease in the score of attention focus (MD=3.61, p<0.001) and attention shift (MD=3.11, p<0.001) of basketball players; the efficiency score (MD=2.22, p=0.006), with significant decreases in the number of points (MD=2.28, p<0.001), field goals made (MD=0.94, p<0.001) and increase in the number of rebounds (MD=-1.06, p<0.001); the tactical performance with significant decreases in the number of ball reversal (BR)(MD=0.56, p=0.030), on-ball screen (ONBS)(MD=1.50, p<0.001) and increase in dribble penetration into the key area (DPKA)(MD=-1.56, p<0.001); the mindfulness state with the significant decrease in the score of mindfulness state (MD=8.39, p<0.001) form pre-test to post-test in MFG. On the other hand, the mindfulness training counteracted the effects of MF on the score of attention focus (MD=0.39, p=1.000) and attention shift (MD=0.28, p=1.000); the efficiency score (MD=-1.78, p p=0.083) including the number of points (MD=-1.44, p=0.056), rebounds (MD=0.17, p=0.058) and field goals made (MD=-0.56, p=0.001); the tactical performance including BR (MD=0.33, p=1.000), ONBS (MD=-0.78, p=0.378) and DPKA (MD=0.22, p=1.000); the score of mindfulness state (MD=-7.33, p<0.001) from pre-test to post-test in MF-MG. Except from pre-test to post-test, just in post-test, results also showed that there was a significant impairment of MF on the score of attention focus (MD=3.78, p<0.001) and attention shift (MD=3.33, p=0.005); efficiency score (MD=2.94, p=0.017) including points (MD=2.50, p<0.001), the number of rebounds (MD=-1.33, p<0.001) and field goals made (MD=1.39, p<0.001); the tactical performance including BR (MD=0.72, p=0.018), DPKA (MD=-1.94, p=0.022) and offball screen (OFFBS) (MD=1.00, p=0.025); the score of mindfulness state (MD=7.67, p=0.032) in MFG compared with CG. On the other hand, results showed the recovery of mindfulness training on the score of attention focus (MD=-3.61, p<0.001) and attention shift (MD=-3.00, p=0.008); efficiency score (MD=-2.67, p=0.092) including points (MD=-3.06, p<0.001) and the number of field goals made (MD=-1.22, p<0.001); the tactical performance including BR (MD=-0.78, p=0.013), DPKA (MD=2.39, p=0.004) ONBS (MD=-1.61, p=0.011) and OFFBS (MD=-1.33, p<0.001); the score of mindfulness state (MD=-16.39, p<0.001) in MF-MG compared with MFG at post-test. In conclusion, MF significant impaired the basketball technical and tactical performance, and mindfulness training was an effective method to counteract the negative effects of MF on basketball technical and tactical performance.